1975
DOI: 10.2320/matertrans1960.16.35
|View full text |Cite
|
Sign up to set email alerts
|

Formation Temperature and Growth Behavior of Thin Plate Martensite in Fe–Ni–C Alloys

Abstract: The authors have previously found that the morphology of martensite in Fe-Ni-0.25%C alloys the transition temperature from the lenticular to the thin plate and the carbon content of Fe-Ni-C alloys was examined by adjusting the carbon content up to 0.9% and the nickel content from 25 to 35%. Furthermore, some features in the progress of transformation to the thin plate martensite from austenite were observed as compared with those of lenticular martensite. The main results obtained are as follows.(1) The transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…It may be concluded that Mo element influences both on the stabilization of austenite and on the martensite start temperature (M S ) like other some alloying elements. Also Maki et al [16,17] investigated the effect of Ms temperature on martensite morphology.…”
Section: Resultsmentioning
confidence: 99%
“…It may be concluded that Mo element influences both on the stabilization of austenite and on the martensite start temperature (M S ) like other some alloying elements. Also Maki et al [16,17] investigated the effect of Ms temperature on martensite morphology.…”
Section: Resultsmentioning
confidence: 99%
“…16,17) Among various 0 martensite morphology, only thin plate martensite has a mobile M/A interface and exhibits a shape memory effect. [18][19][20] As mentioned above, basic characters of lenticular martensite and thin plate martensite are completely different. However, when only midrib is paid attention, substructures and habit planes of midrib and thin plate martensite are quite similar.…”
Section: )mentioning
confidence: 99%
“…Those were known merely to belong to two zones of the martensite, [731] and [951], away taneous appearance of such two different zonal patterns is accounted for by some elongation of reciprocal lattice points, buckling of the foil specimen and so on. Anyway, such a nottwinned structure of the "thin plate" martensite is quite different from a completely twinned one of the thin plate martensites typically observed in Fe-Ni-C alloys (17). Thus, another type of lattice invariant shear (LIS), other than twinning, should occur upon the formation of such a thin plate martensite as presently observed, in order to maintain the invariant plane (a) and (b) are obviously asymmetrical in shape, indicating the martensite crystal to be tetragonal.…”
Section: Variation Of Martensite Substructurementioning
confidence: 78%
“…Maki et al (17) previously found in Fe-Ni-C alloys that the martensite morphology changed from lenticular to thin plate even in an alloy with an identical composition if Ms temperature (or the formation temperature of martensites strain-induced) was decreased. Hence it has been known that a transition temperature exists for the morphological change of an individual alloy.…”
Section: On the Martensite Morphologymentioning
confidence: 99%